Effects of frequency discrimination training on tinnitus: results from two randomised controlled trials - Hoare, Derek J.; Kowalkowski, Victoria L.; Hall, Deborah A. (Springer Verlag, 2012)
That auditory perceptual training may alleviate tinnitus draws on two observations: (1) tinnitus probably arises from altered activity within the central auditory system following hearing loss and (2) sound-based training can change central auditory activity. Training that provides sound enrichment across hearing loss frequencies has therefore been hypothesised to alleviate tinnitus. We tested this prediction with two randomised trials of frequency discrimination training involving a total of 70 participants with chronic subjective tinnitus. Participants trained on either (1) a pure-tone standard at a frequency within their region of normal hearing, (2) a pure-tone standard within the region of hearing loss or (3) a high-pass harmonic complex tone spanning a region of hearing loss. Analysis of the primary outcome measure revealed an overall reduction in self-reported tinnitus handicap after training that was maintained at a 1-month follow-up assessment, but there were no significant differences between groups. Secondary analyses also report the effects of different domains of tinnitus handicap on the psychoacoustical characteristics of the tinnitus percept (sensation level, bandwidth and pitch) and on duration of training. Our overall findings and conclusions cast doubt on the superiority of a purely acoustic mechanism to underpin tinnitus remediation. Rather, the nonspecific patterns of improvement are more suggestive that auditory perceptual training affects impact on a contributory mechanism such as selective attention or emotional state.